Modeling sequential preparation with rheumatoid tonsils in Nineveh for the period 2004-2009 - البدراني, ظافر رمضان; ابراهيم, عمر سالم; اسماعيل, نورا سهيل (Journal of Economics and Administrative Sciences, 2016)
Abstract              In this research will be treated with a healthy phenomenon has a significant impact on different age groups in the community, but a phenomenon tonsillitis where they will be first Tawfiq model slope self moving averages seasonal ARMA Seasonal through systematic Xbox Cengnzla counter with rheumatoid tonsils in the city of Mosul, and for the period 2004-2009 with prediction of these numbers coming twelve months, has found that the specimen is the best representation of the data model is the phenomenon SARMA (1,1) * (2,1) 12  from the other side and explanatory variables using a maximum temperature and minimum temperature, solar brightness , evaporation, rainfall, wind speed, air pressure, for the same period the previous possible modeling preparation with rheumatoid tonsils and in the method of multiple regression, and then compare the results to predict the two models where given methodology X box Jenkins better results in the prediction of the linear regression multi-depending on the standard of the average errors absolute MAE, and these results can help decision makers to develop appropriate strategies to deal with this disease to reduce the preparation of the injured and provide the prerequisites for appropriate treatment.